Bordering Beyond Borders: A Governmentality Analysis of Australia’s Operation Sovereign Borders and Israel’s Externalisation of Asylum Policy - Titan Alramadhan (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2025)
This paper analyses how Australia and Israel transform deterrence into an ethical means of moral control; it investigates how these nations are using the concept of